AL-WUJŪD AL-DZĀTĪ LIL-IMĀM AL-SHĀFI‘Ī FĪ KITĀB DĪWĀN AL-IMĀM AL-SHĀFI‘Ī ‘ALĀ NAẒARIYYAH WUJŪDIYYAH LI- SØREN KIERKEGAARD - Mohammad Rasyid Hidayatullah Roesli; Abdul Basid (Journal of Arabic Literature (JaLi), 2024)
This research aims to uncover the existential choices of Imam Asy-Syafi’i in his poems in the book "Diwan Al-Imam Asy-Syafi’i," as well as to find the similarities and differences in self-existence thinking between him and Søren Kierkegaard. The main object of the research is the poems of Imam Asy-Syafi’i from the book "Diwan Al-Imam Asy-Syafi’i" published by Dar al-Kutub al-Ilmiyah in 2020. This research uses a qualitative approach. This research is based on Søren Kierkegaard's existentialism theory, which emphasizes personal choice, subjectivity, freedom, responsibility, and the religious dimension. Data was collected using the read-and-note technique, followed by data reduction analysis, presentation, and conclusion drawing. The research results show that the poems of Imam Asy-Syafi’i reflect existential choices such as patience, independence, and forgiveness, which align with Kierkegaard's concept of self-existence through subjective, free, and responsible choices, including the religious stage. The fundamental similarity lies in the emphasis on subjective choices and the background of religious thought, while the differences arise from the religious traditions (Islam vs. Christianity) and the roles of the figures (scholar vs. philosopher)